The Causal Relationship between Exports, Imports and Economic Growth in Palestine - Fannoun, Zahra’; Hassouneh, Islam (Journal of Reviews on Global Economics, 2019)
The relationship between exports, imports and economic growth is investigated for the Palestinian economy over the period 2000-2018, using quarterly data. To do so, cointegration test using Johansen’s approach as well as vector error correction technique are used. Findings confirm the presence of long-run equilibrium relationship between exports, imports and output growth. Results also support the existence of bidirectional long-run causality between exports, imports and output growth. As for the short-run causality, findings support both the export-led import and the import-led export hypotheses. Further, imports are found to Granger cause economic growth. Policy makers should be aware of the importance of trade to stimulate economic growth.